Fretting damage behaviors of silicon nitride balls with different sintering aids and processes under grease lubrication. (July 2022) - Wei, Wanxin; Liang, Hanqin; Su, Yunfeng; Fan, Hengzhong; Song, Junjie; Li, Weimin; Hu, Litian; Zhang, Yongsheng
Abstract: Taking silicon nitride (Si3 N4 ) balls prepared using different sintering processes and sintering additives as objects, their tribological properties against bearing steel were investigated under grease lubrication conditions with heavy loads and high-frequency fretting, followed by analyzing the wear and fatigue damage behaviors. The results show that the Si3 N4 balls prepared by adding 5AlEr and using the GPS1850 presented enhanced wear resistance and a low, stable friction coefficient ((6.10 ± 1.06)× 10 −4 mm 2 ). An appropriate increase in the temperature during GPS and selection of a sintering additive with a small cation radius were conducive to improving the wear resistance of Si3 N4 balls. In addition, a strong adhesive friction film was formed through chemical reactions on the wear surface, which further protected the Si3 N4 balls.